OPTIMALISASI TRUST ANGGOTA DAN MASYARAKAT MELALUI SEMINAR PENINGKATAN KOMPETENSI HUKUM BAGI PENGURUS, PENGAWAS DAN PENGELOLA KOPERASI DI KOTA DENPASAR - I Dewa Gede Kresna Wirawan; Putu Siti Firmani (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
This research aims to increase members' and society's trust in cooperatives through seminars to increase legal competency for administrators, supervisors and cooperative managers in Denpasar City. The method used is a qualitative approach through case studies, interviews and observations of 25 randomly selected cooperatives. The results obtained show an increase in participants' understanding of the legal aspects of cooperative management, which is expected to increase transparency and accountability. The active participation of participants shows the high need for legal training, which is responded to through transformative learning theory and trust transformation theory. The positive impact of this seminar includes increasing member and community trust in the Cooperative, which in turn can increase member welfare and contribution to the local economy.